A Comparison of the Nutrient Content of Standard and Vegetarian Childcare Lunches. (7th June 2021) - Jindrich, Caitlin; Hanson, Jennifer; Daniels, Elizabeth
Abstract: Objectives: As consumer interest in plant-based eating has increased, requests for meatless childcare meals have become increasingly common. Although vegetarian meals can be nutrient dense, without proper planning, nutrient inadequacies may occur. The objective of this study was to compare the nutrient content of standard childcare lunches with that of vegetarian alternative lunches. Methods: Data was obtained from childcare centers participating in the Child and Adult Care Food Program and regularly providing a vegetarian meal alternative in addition to their standard meal. Centers that agreed to participate received unscheduled calls in which they were asked to provide menu and food preparation details for both the standard meal and for the vegetarian option served at lunch. Student's t -tests ( P ≤ .05) were used to detect differences in nutrient content. Nutrient values (95% CI) for each set of meals were then compared to reference values representing one-third the Dietary Reference Intake for 3-year-olds. Results: Seven childcare centers provided detailed information for a total of 27 meals. Vegetarian meal substitutions included, beans, vegetarian meat patties, tofu, and sunflower seed butter. However, the most common substitution was cheese which was used to fulfill all or part of the meat/meat-alternative requirement in 70.4% of the meals ( n = 19). Mean values for energy, protein, fiber, vitamin A, vitamin D, iron, total fat, saturated fat, iron, and vitamin B12 did not differ significantly between the two lunch options. The vegetarian lunches were higher in saturated fat ( P = 0.04) and calcium ( P < 0.001). Both lunch options met the reference value for vitamin A, vitamin D, vitamin B12, calcium, and protein. Iron content for both (95% CI: standard 1.61–2.17 mg; vegetarian 1.37–2.7 mg) was below the reference value of 2.31 mg. Conclusions: Aside from the vegetarian lunches being higher in saturated fat, both meals provided comparable nutrient content. Both meal options could be improved upon by the inclusion of more iron-dense foods. The vegetarian meals could be improved upon with less cheese and more plant-based alternatives, such as such as lentils and beans which are good sources of protein but low in saturated fat. Funding Sources: College of Health and Human Sciences and Dr. Carol Shanklin Graduate Research Enhancement Award, Kansas State University.